The prehistory of the Slavic vowel system : (a reply to Mate Kapović) - Kortlandt, Frederik (Array, 2020)
The methodological differences between Kapović and myself are threefold: (1) He disregards the chronological aspects of linguistic developments. As a result, he mixes up elements from different stages of development. (2) He disregards the linguistic system in which developments take place. As a result, he reconstructs typologically improbable linguistic systems. (3) He multiplies the input criteria of his rules in order to arrive at the correct output. The larger the number of input distinctions, the easier it becomes to generate any desired output. A combination of these devices renders his treatment opaque and confuses the issues at hand.